Ethnoreligious Marketing through the Betawi Palang Pintu Culture in Disseminating Islam - Furqan MD, Muhammad; Mahmud, Hamidullah (JURNAL ISLAM NUSANTARA, 2024)
This study aims to find out about the palang pintu in the Betawi tradition that uses various attractions such as silat attractions, pantun exchanges and dustur shalawat as components in the Betawi palang pintu tradition. The palang pintu tradition, which is a Betawi ethnic tradition, is still carried out by the Betawi people who live in the Jabodetabek area, especially the Padepokan Beksi SangHiyang Putih and the Betawi Cultural Village Area Management Unit Setu Babakan. The object of this study is the Betawi community strategy implemented by both Padepokan in promoting the values of da'wah in the palang pintu tradition. The data collection technique in this study uses a qualitative descriptive research method, to reveal the promotional strategies carried out by the Betawi community on the values of da'wah. Research data collection includes observation, documentation and direct interviews at the Padepokan and the Betawi Cultural Village Area Management Unit, data collection from informants who are the founders of the Padepokan and Betawi cultural figures who have long carried out the Palang Pintu tradition. The results of the research show that in the Palang Pintu tradition, promotional strategies are implemented through traditional and religious approaches, such as the promotional strategy carried out, namely reading the Koran and practicing silat to students and teenagers, while the Betawi Cultural Village Management Unit holds the Betawi Cultural Festival, the Palang Pintu Setu Babakan art studio where the Palang Pintu Art Studio is a traditional Palang Pintu art institution as a medium for preserving ancestral traditions.